The benthic-pelagic coupling affects the surface water carbonate system above groundwater-charged coastal sediments - Szymczycha, Beata; Böttcher, Michael Ernst; Diak, Magdalena; Koziorowska-Makuch, Katarzyna; Kuliński, Karol; Makuch, Przemysław; von Ahn, Cátia Milene Ehlert; Winogradow, Aleksandra (Frontiers in Marine Science, 2023)
Submarine groundwater discharge (SGD) can be a significant source of dissolved nutrients, inorganic and organic carbon, and trace metals in the ocean and therefore can be a driver for the benthic-pelagic coupling. However, the influence of hypoxic or anoxic SGD on the carbonate system of coastal seawater is still poorly understood. In the present study, the production of dissolved inorganic carbon (DIC) and alkalinity (AT) in coastal sediments has been investigated under the impact of oxygen-deficient SGD and was estimated based on the offset between the measured data and the conservative mixing of the end members. Production of AT and DIC was primarily caused by denitrification and sulphate reduction. The AT and DIC concentrations in SGD decreased by approximately 32% and 37% mainly due to mixing with seawater counterbalanced by reoxidation and CO2 release into the atmosphere. Total SGD-AT and SGD-DIC fluxes ranged from 0.1 to 0.2mol m-2 d-1 and from 0.2 to 0.3mol m-2 d-1, respectively. These fluxes are probably the reason why the seawater in the Bay of Puck is enriched in AT and DIC compared to the open waters of the Baltic Sea. Additionally, SGD had low pH and was undersaturated with respect to the forms of the aragonite and calcite minerals of CaCO3. The seawater of the Bay of Puck also turned out to be undersaturated in summer (Inner Bay) and fall (Outer Bay). We hypoth​e​size that SGD can potentially contribute to ocean acidification and affect the functioning of the calcifying invertebrates.